The Relationship Between Beginning Reading Skills and Phonemic Awareness in Elementary School Students: A Literature Review - Yulia Angga Anggraina; Anang Sudigdo; Sabarudin Sabarudin (Journal of Education and Teacher Training Innovation, 2026)
Early reading skills are a crucial foundation for developing literacy among students in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD). One of the key abilities that supports success in early reading is phonemic awareness. This study aims to analyze the relationship between early reading skills and phonemic awareness, as well as to identify effective instructional strategies through a literature review approach. The articles were retrieved from the Google Scholar, Garuda, and ScienceDirect databases using the PRISMA guidelines. The selection process was conducted based on inclusion criteria, including articles published between 2016 and 2026, focusing on early reading skills and phonemic awareness among Madrasah Ibtidaiyah (MI) and Elementary School (SD) students, and available in full-text format. Of the 64 articles initially identified, 27 met the inclusion criteria and were selected for further analysis. The findings of the review indicate that phonemic awareness has a strong relationship with early reading skills by enhancing learners' ability to recognize phoneme–grapheme correspondences, decoding skills, and reading fluency. Explicit phonics instruction, phonological games, multisensory approaches, and the use of innovative instructional media have been shown to be effective teaching strategies. This study provides a comprehensive synthesis of the relationship between early reading skills and phonemic awareness, serving as a foundation for the development of more effective early literacy instruction at the Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels.